Jargons in immunisation brochures and its influence on students’ vaccination intention - Mawardi, Nisa Nur Arisyia; Sardi, Janudin; Serip Mohamad, Nur Husna; Anuar, Nadia (Universiti Teknologi MARA, 2025)
This qualitative study identifies the in the Ministry of Health’s National COVID-19 Immunisation Programme brochure and explores the influence of the jargons on university students’ vaccination intentions. Through content analysis, key jargon terms were identified and categorised based on Halliday’s Systemic Functional Linguistics, specifically the ideational metafunction. Following this, semi-structured interviews with three university students revealed varying levels of comprehension regarding technical terms and their influence on vaccination decisions. Findings also indicate that while the brochure conveys essential scientific information, its complex language may hinder understanding, emphasising the need for clearer communication to foster vaccine acceptance. This study also highlights the importance of accessible health messaging in promoting public health initiatives.